2011
DOI: 10.20870/productions-animales.2011.24.1.3236
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation des animaux d’élevage aux multiples contraintes des régions chaudes

Abstract: En zones difficiles, la pérennité des systèmes d’élevage repose sur la capacité des animaux à survivre, se reproduire et maintenir un niveau de production en situation de fortes contraintes. Les principales contraintes auxquelles les animaux doivent faire face en régions chaudes, sont le climat (température et humidité), la sous-nutrition et les pathologies. Chez les monogastriques comme chez les ruminants, les caractéristiques anatomiques et le comportement alimentaire constituent les principaux facteurs de r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 99 publications
(131 reference statements)
0
2
0
3
Order By: Relevance
“…This increase in this rate would be due to hypoxia. In fact, the polypnea increases the pulmonary gas exchanges leading the animal to hypoxia state rapidly (Mandonnet et al, 2011), which is responsible of increasing in hemoglobin rates in the red blood cells. However, the hemoglobin rates obtained in this study are lower than those found by Albokhadaim (2012) for indigenous chickens in Arabie Saoudite.…”
Section: Discussion:-mentioning
confidence: 99%
“…This increase in this rate would be due to hypoxia. In fact, the polypnea increases the pulmonary gas exchanges leading the animal to hypoxia state rapidly (Mandonnet et al, 2011), which is responsible of increasing in hemoglobin rates in the red blood cells. However, the hemoglobin rates obtained in this study are lower than those found by Albokhadaim (2012) for indigenous chickens in Arabie Saoudite.…”
Section: Discussion:-mentioning
confidence: 99%
“…Goats, for instance, are highly adaptable to harsh conditions and can conserve urine during droughts, making them an ideal option for arid environments [10,102]. Furthermore, native breeds and species that have evolved in tropical climates are typically more resistant to endoparasites and ticks [97,103,104]. Selective breeding programs can help increase the resistance of sheep to nematodes, which has been proved through classical quantitative methods [105].…”
Section: Ethiopiamentioning
confidence: 99%
“…Ryding et al (2021) ont renchéri en indiquant que l'agrandissement de la surface des oreilles constitue un mécanisme de régulation des échanges thermiques. Par ailleurs, Mandonnet et al (2011) Se realizó una caracterización morfométrica en la población ovina Djallonké de Benín analizando múltiples variables con el fin de apreciar la diversidad intrarracial y orientar eficazmente los planes de mejora genética. En total se fenotiparon 488 hembras y 74 machos utilizando 15 variables cuantitativas.…”
Section: Analyses Multivariéesunclassified